Human Immunodeficiency Virus Infection And Hypertension. Is There a Connection?. (6th December 2017) - Sanidas, Elias; Papadopoulos, Dimitris P; Velliou, Maria; Tsioufis, Kostas; Barbetseas, John; Papademetriou, Vasilios
Abstract: Data support that hypertension (HTN) is prevalent among human immunodeficiency virus (HIV) patients contributing to increased risk of cardiovascular disease. Immunodeficiency and prolonged antiretroviral treatment along with common risk factors including older age, male gender, and high body mass index might conduce to greater incidence of HTN. The purpose of this review was to summarize recent evidence of the increased cardiovascular risk in these patents linking HIV infection to HTN.